HUBUNGAN HIGIENE SANITASI DENGAN KUALITAS MIKROBIOLOGIS PADA MAKANAN GADO-GADO DI KECAMATAN TEMBALANG KOTA SEMARANG - Yuniatun, Tuti; Martini, Martini; Purwantisari, Susiana; Yuliawati, Sri (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Gado-gado is one of traditional foods from Indonesia which sold in Tembalang District. Gado-gado is made from various vegetables mixed with peanut sauce, served at temperature 5-60oC which is the